2012
DOI: 10.1097/qad.0b013e3283573244
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic insights into regional HIV transmission

Abstract: Objectives Despite prevention efforts new HIV diagnoses continue in the Southern US, where the epidemic is characterized by significant racial/ethnic disparities. We integrated phylogenetic analyses with clinical data to reveal trends in local HIV transmission. Design Cross-sectional analysis of 1671 HIV-infected individuals each with one B-subtype pol sequence obtained during chronic (82%; UNC Center for AIDS Research Clinical Cohort) or acute/recent (18%; Duke/UNC Acute HIV Consortium) infection. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 39 publications
3
48
1
Order By: Relevance
“…Similar results were reported with small sequence datasets when other parts of HIV-1 genome sequences were analyzed 20-22 . This epidemic pattern was different from those in MSM populations in other countries, in which the MSM sequences intermingled with sequences from general HIV-1 infected individuals 40,41 . This unique epidemic pattern indicated that only limited introductions of HIV-1 strains from the general population became predominant strains in the MSM populations in China and the close network resulted in transmission chains mainly among MSM, allowing spreading of the same viruses in all geographic regions across the country.…”
Section: Discussioncontrasting
confidence: 77%
“…Similar results were reported with small sequence datasets when other parts of HIV-1 genome sequences were analyzed 20-22 . This epidemic pattern was different from those in MSM populations in other countries, in which the MSM sequences intermingled with sequences from general HIV-1 infected individuals 40,41 . This unique epidemic pattern indicated that only limited introductions of HIV-1 strains from the general population became predominant strains in the MSM populations in China and the close network resulted in transmission chains mainly among MSM, allowing spreading of the same viruses in all geographic regions across the country.…”
Section: Discussioncontrasting
confidence: 77%
“…This cut-off has been used in multiple similar analyses 16,21,2630 . We considered clusters as groups of greater than two members since transmission pairs may have entered care as part of partners testing and may less likely represent sources of continuous, ongoing transmission 17,27 .…”
Section: Methodsmentioning
confidence: 99%
“…21 The HIV-1 pol gene has been used for phylogenetic reconstruction of transmission events 22 and for HIV cluster analysis over the past decade. [3][4][5][6][7]9,[11][12][13]15,19,20,[23][24][25][26][27][28][29][30][31][32] Other HIV-1 genes have also been used for linkage analysis in discordant couples. 33,34 A weaker clustering of subgenomic regions, as compared with the near full-length genome sequences, was demonstrated for HIV-1C from Ethiopia, 35 although the set of viral sequences analyzed was relatively small.…”
Section: Introductionmentioning
confidence: 99%